Isolasi Bakteri Rhizosfer Resisten Pestisida dan Herbisida pada Berbagai Jenis Tutupan Lahan - Apriliya, Indah; Prasetyo, Dedy; Selvany, Remila (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2020)
The use of microbes as bioremediation agents is an alternative strategy to reduce residual or pesticide resistance. This study utilized rhizosphere microbes from various land covers as isolates. Soil samples used came from the rhizosphere of papaya, bamboo, peanuts, rice fields, maize, sweet potatoes, forest plants, cucumbers and guava. Isolation was carried out using Minimum Salt Agar (MSM) media which added 50 and 100 ppm of pesticide or herbicide. Microbes that were able to grow at a concentration of 100ppm were used as the selected isolates. Furthermore, the isolates were characterized by morphology and physiology such as; gram test, motility, pathogenicity, oxygen demand. As well as testing the microbial activity of selected isolates on the soil through a soil respiration test contaminated with herbicides and pesticides using sterile soil. A total of 5 selected isolates were used in the respiration test, namely with the code JMH, SH, HH, JP and TP. Of the 3 isolates that have the potential to degrade pesticides, the isolates with the JP code of 15.6 mg C-CO2 / g / day produced the highest respiration value. Meanwhile, of the 2 isolates had the potential to degrade herbicides, the isolates with the SH code of 9.6 mg C-CO2 / g / day produced the highest respiration value. These isolates have potential as biodegradation agents for pesticides and herbicides, so it is necessary to continue for further analysis regarding quantification and the mechanism of biodegradation.